PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI DINAS PENDIDIKAN, KEPEMUDAAN DAN OLAHRAGA KOTA DENPASAR - Wulandari, Anak Agung Sagung Putri; Lukman, Juwita Pratiwi; Wirantari, I Dewa Ayu Putri (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
The purpose of this study is to analyze and test the impact of leadership and organizational culture on employee performance. This study was conducted at the Denpasar City Education, Youth, and Sports Agency (Disdikpora), and involved a randomly selected sample of 95 employees. Data obtained from the distribution of questionnaires are described in the analysis. This study uses several linear regression analyses using hypothetical tests (t-tests and f-tests) as data processing methods. The results of this study indicate (1) Leadership style has a positive and significant impact on employee performance at the Denpasar City Education and Sports Agency. (2) Organizational culture also has a positive and significant impact on employee performance, because the stronger the organizational culture is proportional to the stronger employee performance.